High-Fat Diets-Induced Metabolic Disorders to Study Molecular Mechanism of Hyperlipidemia in Rats - harfi maulana; Ahmad Ridwan (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
Hyperlipidemia is a lipid metabolism disorder occurring due to consumption of a high-fat diet (HFD), which contributes to atherosclerosis and cardiovascular disease development. HFD causes metabolic problems in Rodentia animals like human metabolic abnormalities, making it a popular model for studying the signaling systems involved. Hyperlipidemia is a condition in which the body's cholesterol levels elevate. In recent years, several studies have investigated the relationship between HFD feeding and hyperlipidemia and signaling pathways involved in cholesterol homeostasis. However, this signaling mechanism in lipid metabolism has not been fully explained, so additional analysis is needed. The present study aimed to investigate the mechanism that occurs from hyperlipidemia due to HFD feeding. The method used is a literature review approach following the PRISMA scheme for selecting the primary literature, including identification, screening, eligibility test, and inclusion. Eleven articles included primary literature with credibility (H-index) of 20, 33, 71, 92, 93, 162, 180, 192, and 332 (six articles from Q1 journals and five from Q2 journals). Long-term administration of HFD directly affects lipid metabolism, including an increase in the concentration of total cholesterol, triglycerides, LDL, and a decrease in HDL concentration, followed by an increase in body weight. In addition, HFD also disrupts adipose tissue and insulin resistance. The conclusion of this study is that HFD can cause hyperlipidemia either directly or indirectly by inducing insulin resistance, which contributes to lipid metabolism disorders.